The Architecture of the Virtual World - Sugesti Retno Yanti (Universitas Atma Jaya Yogyakarta, 2023)
The development of artificial intelligence-based virtual reality technology offers the potential of the digital world as an alternative activity space for humans. The virtual world is expected to complement the shortcomings of the natural world and meet human needs that cannot or are difficult to realize in the real world. The real world is formed by physical matter, while the virtual world comprises bits that cause a considerable difference between the two. This study aims to recognize the positive and negative potential due to differences between the real and virtual worlds concerning architecture. The goal is to answer how quickly the architecture of the virtual world can be put into practical use and dominate human life. The method used is the exploration of libraries and the internet, which are reviewed qualitatively. The results show that the idea of humans still dominates the world of virtual architecture as its creators. However, artificial intelligence can give new ideas beyond what humans think. Therefore, the virtual architectural world gives both positive and negative potential concerning differences in character from the real architectural world.